The Effect of Corporate Sustainability Performance Moderated by Liquidity, Stock Price Volatility, Institutional Ownership, And Concentrated Ownership On Profitability - Eryda, Reny; Nalurita, Febria (Universitas Wiralodra, 2024)
This research needs to be done to develop previous studies by adding other variables, especially non-economic variables. This study aims to analyze corporate sustainability performance (CSP) controlled by company size and leverage variables on profitability moderated by liquidity, concentrated ownership, stock price volatility, institutional ownership in consumer goods companies listed on the IDX from 2018 to 2022. This study adds institutional ownership and concentrated ownership as moderating variables as well as company size and the use of debt (leverage) or loans as control variables. The sample withdrawal method in this study used a purposive sampling method of 37 companies with a total sample size of 185 with the regression results of the fixed effect model equation, and random effect. The results of this study indicate that there is no significant effect of CSP on profitability, liquidity moderates the effect of CSP on profitability, stock price volatility does not moderate the effect of CSP on profitability, concentrated ownership does not moderate the effect of CSP on profitability, institutional ownership moderates the effect of CSP on profitability and there is a significant effect of company size and debt use on profitability. Managerial implications to increase CSP and probability, the company's efforts include increasing the liquidity ratio, being more careful in taking debt and must ensure the company's ability to cover the debt. In addition, it seeks to improve performance, innovate and be responsive and sensitive to reading market opportunities